2012
DOI: 10.1371/journal.pone.0030946
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of D222G and Q223R Hemagglutinin Mutants of Pandemic (H1N1) 2009 Influenza Virus in Japan between 2009 and 2010

Abstract: BackgroundIn April 2009, a novel swine-derived influenza A virus (H1N1pdm) emerged and rapidly spread around the world, including Japan. It has been suggested that the virus can bind to both 2,3- and 2,6-linked sialic acid receptors in infected mammals, in contrast to contemporary seasonal H1N1 viruses, which have a predilection for 2,6-linked sialic acid.Methods/ResultsTo elucidate the existence and transmissibility of α2,3 sialic acid-specific viruses in H1N1pdm, amino acid substitutions within viral hemaggl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…Our results support the suggestion that substitution at HA position 222 is associated with pdm09 pathogenicity, with variants appearing spontaneously during the two pandemic waves in Mexico. Some reports and sequence data have demonstrated that 222 variants appeared in the early phases of the pandemic, increased during 2009–2010 influenza season and have reduced to their present levels during 2010–2011 and 2011–2012 influenza season [30,31]. Bacterial infection or coexisting conditions do not appear to be major contributing factors to the severity (Table  2).…”
Section: Discussionmentioning
confidence: 99%
“…Our results support the suggestion that substitution at HA position 222 is associated with pdm09 pathogenicity, with variants appearing spontaneously during the two pandemic waves in Mexico. Some reports and sequence data have demonstrated that 222 variants appeared in the early phases of the pandemic, increased during 2009–2010 influenza season and have reduced to their present levels during 2010–2011 and 2011–2012 influenza season [30,31]. Bacterial infection or coexisting conditions do not appear to be major contributing factors to the severity (Table  2).…”
Section: Discussionmentioning
confidence: 99%
“…However, the severity of the disease can be affected by a number of other factors. In humans, several specimens possessing D222G substitution were also obtained from mild H1N1pdm cases during the first (May 2009) and second (Dec 2010) waves of the epidemic in Japan (21). In addition to the D222G substitution, two other changes D187E and Q223R were recognised.…”
Section: Discussionmentioning
confidence: 99%
“…Newly emergent influenza A viruses may have been dual specific but not exclusively α2,6-SA-specific during the early phase of the pandemic and adapted during multiple cycles of human-to-human transmission (Yasugi et al, 2012). Further investigation is required to determine the proportion of α2,3-tropic and α2,6-tropic viruses found in tissues and organs infected with other human-, avian-, and swine-derived influenza viruses.…”
Section: Discussionmentioning
confidence: 99%